Thermal Performance Analysis of Heat Pipe Heat Exchanger Using Porous Media Modeling - Lee, Seungjae; Kim, Yunseo; Geum, Gyohoon; Kang, Sukkyung; Shin, Dong Hwan; Lee, Seong Hyuk; Lee, Jungho; Lee, Hyoungsoon (Transactions of the Korean Society of Mechanical Engineers, B, 2023)
Unlike conventional heat exchangers, HPHX employs heat pipes for more efficient heat transfer. However, augmenting heat exchange efficiency by adding thin fins to the heat pipe’s exterior necessitates intricate grid-based interpretation, resulting in diminished accuracy dur to the high computational costs involved. Here, we employed a porous media modeling approach to the external fin area of the heat pipe to conduct a thorough computational analysis of HPHX. Variations in heat transfer rate and effectiveness in the heat exchanger were extensively investigated based on different porous media modeling methods. These findings offer a methodological advancement in computational analysis for HPHX heat exchangers, enhancing the precision of predicting thermal and fluid performance.
Keywords: Computational analysis; Computational costs; Grid-based; Heat exchange efficiency; Heat pipe heat exchanger(HPHX; Heat pipe heat exchangers; Nonequilibrium model; Porous medium model; Thermal performance analysis; Thin fins; Heat Pipe Heat Exchanger(HPHX; Non-Equilibrium Model; Numerical Simulation; Porous Media Model